Analisis Perubahan Proses Pembelajaran Daring Ke Luring Di Masa Pandemi Covid-19 - Rohmat Mulyana Sapdi; Siti Zahra Meydina Salsabila; Hamdan Sugilar; Cucu Komala (UIN Sunan Gunung Djati Bandung, 2023)
Switching the math learning process from online to offline has many implications and is often a problem when readjustment is not possible. This is due to the significant difference in the implementation of online learning that has been switched offline. The survey method used is a qualitative survey method with a descriptive survey style. The purpose of this study is to identify changes in math learning, the impacts that are occurring, and the barriers teachers face in dealing with changes in math learning from online to offline during the Covid-19 pandemic. Switching from online to offline math learning has many positive implications. There are some negative effects and barriers for teachers in the limelight. The process, impact, and limitations of offline math learning have been improved compared to online math learning